Kombinasi Peran Model TAM dan CARTER Terhadap Optimalisasi Kepuasan Nasabah Mobile Syariah Banking di Masa Pandemi Covid-19 - Garini Kartika; Segaf Segaf (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background - During the covid-19 pandemic, Islamic banking companies are currently utilizing technology, namely mobile banking by providing easy, effective, and efficient services in banking access to growing customer satisfaction of Islamic banks. Purpose - To determine the combination of the role of the TAM and CARTER models in optimizing customer satisfaction for Mobile Syariah Banking in Malang City during the Covid-19 Pandemic. Design/ Methodology/ Approach – Using quantitative methods by distributing research questionnaires to 100 customers of mobile Syariah banking in Malang City. Using cluster sampling technique by selecting areas in Malang City covering five sub-districts in Malang City, namely Kedungsaatan, Sukun, Klojen, Blimbing, and Lowokwaru. Results and Discussion - Based on the results of research on sharia mobile banking customers in Malang City during the Covid-19 pandemic, the aspects of Usability and Reliability were prioritized over other aspects, but overall the aspects of Ease, Usability, Compliance, Assurance, and Reliability also affect customer satisfaction in using mobile Syariah banking in Malang City during the Covid-19 Pandemic. Conclusion - the use of Islamic banking mobile banking customers can feel satisfaction, namely with the use and reliability. By providing benefits in using mobile banking and good service to provide fast, complete, and sustainable transactions, customers can feel the satisfaction of using Islamic bank mobile banking. Research Limitations - Considering that the discussion about the theory of the influence of this research variable is very broad, this discussion will address the variables of convenience, usability, compliance, reliability, and assurance of customer satisfaction